PROFESSIONAL GROWTH AS A GUARANTEE OF QUALITY EDUCATION: EVALUATION AND SUPPORT SYSTEM FOR CHILDREN’S MUSIC SCHOOL TEACHERS - Abdurayimov Faxriddin Muxammadali o‘g‘li (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
This article examines the importance of continuous professional development among teachers at children’s music schools and how effective evaluation and support systems contribute to improved educational outcomes. It explores current practices in assessing teaching performance, offering methodological guidance, and providing motivation for self-development. The article emphasizes that well-structured support systems for music educators are key to ensuring high-quality and student-centered teaching in arts education institutions.